'Winners, Regardless'?: Racial Politics, Civil Rights Struggles, and the 1950 Track and Field Tour of South Africa. Issue 8 (15th July 2022) - Dyreson, Mark; M. Sikes, Michelle
ABSTRACT: In 1950 as the Civil Rights Movement gathered momentum in the US and apartheid policies hardened in South Africa, the American Amateur Athletic Union sponsored a tour by US track and field all-stars to South Africa. The controversial 1950 venture, following an original 1931 trek and a 1938 trip cancelled after objections to the exclusion of Black athletes from the team, drew hostile fire from a variety of groups in the US went it leaked to the press that only white American athletes were invited. This lily-white American touring squad was selected at a national championship meet held in the national capital region surrounding Washington, DC, created a public relations firestorm. It also inspired many commentators in the US to link racial segregation in the US to South African variants, particularly since Black American athletes were not only excluded from the international tour but from the official hotel of the championship meet, the infamous Willard Hotel open only to whites in the nation's capital. These Cold War era sagas of race and sport sparked an early focus by Civil Rights groups on connecting the struggle against colour lines in the US to the struggle against colour lines in South Africa.